Escala de identificação de dotação e talento : construção de instrumento, evidências de validade e precisão - Freitas, Márcia de Fátima Rabello Lovisi de (2016)
The Munich Model of Giftedness unites individual and environmental characteristics in a single scheme for the identification and development of giftedness and talent (G&T). In this model, natural abilities are called predictors, individual and environmental variables are called moderators and measures of observable talent are called criteria variables. There are seven predictors in the model that reflect the domains for G&T, intellectual abilities, creative abilities, social competence, practical intelligence, artistic abilities, musicality and psychomotor skills. In this thesis, the goal was to design a scale for the identification of G&T characteristics in students in their 4th, 5th and 6th years of primary school, through teacher nomination, as well as analyze their evidence of content validity, internal structure validity, reliability and convergent validity. To achieve the proposed goals, a series of four studies was performed: construction of the scale items; investigation of evidence of content validity based on specialists’ analyses; investigation of evidence of internal structure validity and analysis of internal consistency through teacher nomination, and investigation of evidence of convergent validity based on the correlation with the Raven's Progressive Matrices, in a sample of students. The 120 initial items of the scale were based on predictors of the Munich Model of Giftedness and complementary theories that helped in defining domains. The experts evaluated these items and proposed changes in some items, while others were excluded for not exceeding a minimum ratio of interjudge agreement. The second version of the scale consisting of 98 items, was applied to 16 teachers of 4th, 5th and 6th year primary school students which evaluated 433 students. The results of the factor analysis from this application indicated that the scale has a well-defined three-factor structure that encompasses items from the seven predictors of the model, which explains 54.8% of the total variance. The internal consistency of the instrument and for each three factors can be considered good to excellent. The scale scores also presented moderate to strong correlations with the Raven's Progressive Matrices, providing evidence for the convergent validity of the instrument. Despite the satisfactory results found, further studies are needed to increase the representativeness of the participant sample, and of the analysis for standardizing the instrument in order to conduct analyses to establish norms for interpretation of scores obtained using this instrument.